Perlakuan Benih dengan Agen Hayati dan Pemupukan P untuk Meningkatkan Pertumbuhan Tanaman, Hasil, dan Mutu Benih Padi - Agustiansyah, ,; Ilyas, Satriyas; Sudarsono, ,; Machmud, Muhammad (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2013)
The objective of the study was to determine the effect of seed treatment on growth, seed quality, P fertilizer utilization, and rice production in the glasshouse. The experiment was conducted in a split plot design with three replications from January to June 2010.The main plots were P fertilizer rates (0, 50, and 100 kg SP-36 ha-1), and sub plots were (1) negative control (seeds were not inoculated by Xanthomonas oryzaepv. oryzae(Xoo) and without seed treatment); (2) positive control (seeds were inoculated by Xoo); (3) seeds were inoculated by Xoo and immersed in Pseudomonas diminutaA6 suspension; (4) seeds were inoculated by Xoo and immersed in Bacillus subtilis5/B suspension; (5) seeds were inoculated by Xoo and immersed in P. diminutaA6 + B. subtilis5/B suspension; (6) matriconditioning + P. diminutaA6, (7) matriconditioning + B. subtilis5/B, and (8) matriconditioning + P. diminutaA6 + B. subtilis5/B. The results showed that seed treatment with biological agents P. diminutaA6, seed treatment with P. diminutaA6 + B. subtilis5/B were the best seed treatments to improve plant growth and yield of rice. Treatment with matriconditioning + P. diminutaA6 + B. subtilis5/B was the best treatment to enhance seed germination. Soaking the seeds in B. subtilis5/B suspension or P. diminutaA6 + B. subtilis5/B suspension reduced the use of P fertilizer, based on the number of grain, total number of grain, percentage of grain per panicle. The highest seed yield obtained from both treatments was with the application of P fertilizer 50 kg ha-1. Keywords: biopriming, matriconditioning, rhizobacteria, seed viability, seed vigorABSTRAK